Caffeine-containing drinks - A cause of arrhythmias? - Myerson, S; Samarasinghe, Y; Taylor, C; Feher, MD (2002)
Caffeine-containing drinks are increasingly available but excessive consumption can give rise to health hazards. A case is described here of a 31 year old man with no history of cardiovascular disease but a very high caffeine intake; he developed atrial fibrillation, which required treatment with flecainide. He has reduced his caffeine intake and remains well to date.